THE USE OF FAMILY FOOTBALL MEDIA TO IMPROVE GROSS MOTOR SKILLS IN GROUP A - Nur Anisa, Puput; Yulianty S, Nadya (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
Gross motor skills play a crucial role in early childhood development, as they are closely related to balance, muscle strength, agility, coordination, and overall physical growth. These skills form the foundation for children’s ability to participate actively in daily activities and structured learning experiences. This study was conducted at Mutiara Insani Kindergarten and aimed to improve children’s gross motor skills through the use of Family Ball learning media. The research involved 16 children aged 4–5 years and employed the Classroom Action Research (CAR) method using a cycle model implemented in two cycles. Data were collected through observation and documentation techniques to assess children’s progress during the learning activities. The Family Ball media consists of several balls of different sizes representing family members, such as father, mother, older siblings, and baby, which were used in various physical activities. The results of the study showed a significant improvement in children’s gross motor skills, particularly in throwing, catching, rolling, and kicking the ball. In addition, children became more active, agile, enthusiastic, and confident during learning activities. These findings indicate that Family Ball media is effective as a thematic learning model and as an extracurricular activity to stimulate gross motor skill development in early childhood.